Synthactic Study of Verba Phrases in The Novel Princess Izatunnuha by Salma Izatunnuha - Puja Ayu Asy’ari; Aninditya Sri Nugraheni (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The research "Analysis of Verbal Phrases in Princess Sayaka's novel by Salma Izatunnuha in terms of Syntactic Studies" is motivated because today many novels are written not only from adults, even children and adolescents have dared to express their ideas and creativity in a work, especially works contained in the KKPK (Small-Owned Work) published by DAR! Mizan Where KKPK is a place to put the works of the nation's children to be published in writing, both in the form of novels or short stories. Because the novels or other works contained in the KKPK (Small-Owned Works), are specialized containers for children and adolescents aged 7-12 years, the sentences used pay attention to the sentence patterns that can be understood by their circles. This study aims to analyze the verb phrases found in the 12-year-old Prinsess Sayaka Novel by Salma Izatunnuha. This research belongs to a descriptive qualitative research. Where the data used in this study in the form of a set of words that form a verb phrase in Novel Princess Sayaka. The process of collecting data is by reading, marking and taking notes. The results of this study are that there are several verb phrases in the novel Princess Sayaka, the form of the phrase used is also a word that is often found in everyday life. Based on the results of research conducted along with the discussion, the conclusion is the verb phrase is a phrase in which the central element is a verb or verb. Verbal phrases have 3 types, namely: modification verb phrases, coordinative verb phrases, and apositive verb phrases. Of these three types of verb phrases, in Princess Sayaka's novel there are only modificative and coordinative verb phrases.